Probiotic Products in Canada with Clinical Evidence: What Can Gastroenterologists Recommend? - Gregor Reid; Kingsley Anukam; Tara Koyama (Canadian Journal of Gastroenterology)
Probiotics, defined as ‘live microorganisms, which when administered in adequate amounts, confer a health benefit on the host’, are finally becoming an option for gastroenterologists in Canada, after being available for many years in Japan, Europe and the United States of America. Unfortunately, Health Canada and the US Food and Drug Administration have not controlled the use of the term ‘probiotic’ or put into place United Nations and World Health Organization guidelines. The net result is that a host of products called ‘probiotics’ are available but are not truly probiotic. The aim of the present review was to discuss the rationale for probiotics in gastroenterology, and specifically examine which products are options for physicians in Canada, and which ones patients might be using. It is hoped that by clarifying what probiotics are, and the strengths and limitations of their use, specialists will be better placed to make recommendations on the role of these products in patient care. In due course, more clinically documented probiotics will emerge, some with therapeutic effects based on a better understanding of disease processes.